Door-to-needle delays in minor stroke: A causal inference approach - Rostanski, Sara K. (Stroke, 2017)
BACKGROUND AND PURPOSE: Thrombolysis rates among minor stroke (MS) patients are increasing due to increased recognition of disability in this group and guideline changes regarding treatment indications. We examined the association of delays in door-to-needle time (DTN) with stroke severity. METHODS: We performed a retrospective analysis of all stroke patients who received tissue plasminogen activator in our emergency department between 7/1/2011 and 2/29/2016. Baseline characteristics and DTN were compared between MS (NIHSS ≤5) and non-minor strokes (NIHSS>5). We applied causal inference methodology to estimate the magnitude and mechanisms of the causal effect of stroke severity on DTN. RESULTS: Of 315 patients, 133 (42.2%) had NIHSS ≤5. Median DTN was longer in MS than non-minor strokes (58 vs. 53 minutes, P=0.01); fewer MS patients had DTN ≤45 minutes (19.5% vs. 32.4%, P=0.01). MS patients were less likely to use Emergency Medical Services (EMS) (62.6% vs. 89.6%, P<0.01) and to receive EMS pre-notification (43.9% vs. 72.4%, P<0.01). Causal analyses estimated MS increased average DTN by 6 minutes, partly through mode of arrival. EMS pre-notification decreased average DTN by 10 minutes in MS patients. CONCLUSION: MS had longer DTN times, an effect partly explained by patterns of EMS pre-notification. Interventions to improve EMS recognition of MS may accelerate care.